To study the effect of Al/water nanofluids on thermo-hydraulic performance of single-pass cross-flow compact heat exchanger - Singh, Suveg (My University, 2015)
Miniaturization of thermal systems along with ultra-high performance is one of the essential need for industrial, domestic and automobile cooling systems. Thermal conductivity of the heat transfer fluids have a vital role in the development of energyefficient fluids. Poor thermal conductivity of conventional fluids such as water, ethylene glycol and oils put a constraint on the development of energy efficient thermal devices. Nanofluids, seem as panacea for thermal equipments, which are the suspension of nano sized particles (typically 1-100 nm) in base fluids provided by nanotechnology. In recent years, nanofluids gained a lot of attraction because of their superior thermal properties over base fluids. Nanofluids have unique features, which are significantly different form conventional heat transfer fluids prepared by millimeter or micrometer sized particles. A lot of work has been done on the metal oxide based nanofluids, however few researchers studied the effect of metal based nanofluids on the performance of thermal devices. In the present work, effect of Al/water nanofluids on the thermo-hydraulic performance of a single pass cross flow compact heat exchanger has been investigated. Nanofluids were prepared by dispersing metal basis aluminum nanoparticles of 100 nm size into double distilled water. Various thermo-physical properties such as density, viscosity and thermal conductivity of nanofluids and their variation with fluid temperature were measured experimentally. Experiments were performed on single pass cross flow compact heat exchanger by varying various parameters such as hot fluid flow rate, velocity of cold air, nanoparticle volume concentration and inlet temperature of hot fluid. Performance of heat exchanger was investigated by studying the effect of these parameters on hot and cold fluid side Nusselt number and friciton factor and Colburn factor was also studied for cold fluid side. It was observed that hot fluid side Nusselt number was improved by 3.23% and 4.65% for 0.1% and 0.2% concentration of nanofluid, respectively at 45°C inlet fluid temperature as compared to distilled water. Colburn factor was increased by 11.11% and 13.9% for 0.1% and 0.2% nanoparticle volume concentration of nanofluids, respectively at 45°C inlet fluid temperature with respect to base fluid. Hot fluid side friction factor was increased by 14.38% and 21.2748% for 0.1% and 0.2% nanoparticle volume concentrations of nanofluids, respectively with respect to distilled water but it was decreased by 2.63% and 9.50%, when temperature was increased from 45 to 50 and 55°C.
ME-Thermal Engineering-Thesis
Keywords: Heat Exchanger; nanofluids; Aluminium; Thermo-hydraulic; Compact; mechanical engineering; thermal engineering; med